2005
DOI: 10.3319/tao.2005.16.4.775(gig)
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Prediction Studies Using Radon as a Precursor in N-W Himalayas, India: A Case Study

Abstract: 30 -34°N, 74 -78°E). The influence of meteorological parameters viz. temperature, rainfall, relative humidity and wind velocity on radon concentration was qualitatively evaluated. The radon exhalation showed positive correlation with temperature, rainfall, relative humidity and negative correlation with wind velocity. Both positive and negative radon anomalies were recorded. The study reveals the precursory nature of radon anomalies and their correlation with microseismic events in 62% of the cases but predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 31 publications
1
46
0
1
Order By: Relevance
“…Various statistical methods have been used by different authors in the past (Guerra and Lombardi, 2001;Fu et al, 2005;Yang et al, 2005;Walia et al, 2005) for identifying possible threshold values of the anomalous radon concentrations. A very common approach could be to examine the difference between radon peak and the mean value of the radon concentration for a few months or a year.…”
Section: Correlation Of Radon Concentration With Seismic Eventsmentioning
confidence: 99%
“…Various statistical methods have been used by different authors in the past (Guerra and Lombardi, 2001;Fu et al, 2005;Yang et al, 2005;Walia et al, 2005) for identifying possible threshold values of the anomalous radon concentrations. A very common approach could be to examine the difference between radon peak and the mean value of the radon concentration for a few months or a year.…”
Section: Correlation Of Radon Concentration With Seismic Eventsmentioning
confidence: 99%
“…Other works (Choubey et al, 1997;Virk and Walia, 2000;Walia et al, 2003Walia et al, , 2005aWalia et al, , 2005b) focused on radon monitoring in waters and soils for health hazard assessment and as a tool for earthquake prediction studies. Few published studies have reported chemical (Gupta, 1996) and isotopic data (Giggenbach et al, 1983) of the thermal waters.…”
mentioning
confidence: 99%
“…Changes in radon and other soil-gas concentrations, and other parameters, before and after earthquakes have been widely reported (Asada, 1982;Chyi et al, 2001;Climent et al, 1999;Crockett et al, 2006a;Crockett & Gillmore, 2010;Igarishi et al, 1995;Kerr, 2009;Koch & Heinicke, 1994;Planinic et al, 2000;Plastino et al, 2002;Wakita, 1996;Walia et al, 2005;Walia et al, 2006;Zmazek et al, 2000). However, in the majority of such radon cases, changes in magnitude in single time-series have been reported, often large changes recorded using integrating detectors, and the majority of radon time-series analysis is reported for single time-series (e.g.…”
Section: Introductionmentioning
confidence: 99%